An examination of the unintended consequences of the legalization of recreational marijuana on alcohol-related behaviors - Chamlin, Mitchell B. (Journal of crime and justice, 2021)
This paper focuses on the unintended consequences of the legalization of recreational marijuana within the state of Colorado. Toward this end, we examine the impact of our intervention series on tax revenue from the sale of all varieties of liquors (beer, wine, and spirits) and the number of fatal motor vehicle crashes involving alcohol. The results from the interrupted time series analyses indicate the legalization of recreational marijuana significantly increased tax revenue from alcohol sales and the number of fatal motor vehicle crashes involving alcohol. The implications of these findings for the evaluation of social policy are discussed.